Mild and Metal-Free Diastereoselective Synthesis of N-tert-Butanesulfinylamines by Using Tetrakis(dimethylamino)ethylene - Spitz, Cédric; Lin, Anna; Terme, Thierry; Vanelle, Patrice (Synthesis, 2014)
A mild and metal-free diastereoselective synthesis of N-tert-butanesulfinylamines was developed by using a strategy based on tetrakis(dimethylamino)ethylene. Good yields and diastereoselectivities were achieved by addition of o-nitrobenzyl chloride or 4-[4-(chloromethyl)phenyl]-1,2-dimethyl-5-nitro-1H-imidazole to readily available N-tert-butanesulfinimines.
Keywords: sulfinimines; diastereoselectivity; amines; metal-free; chiral auxiliary